2006
DOI: 10.1016/s1808-8694(15)30057-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passive smoke inhalation on the vocal cords of rats

Abstract: It was concluded that the passive inhalation of cigarette smoke yields important morphological changes in the vocal fold epithelium, which may progress to neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Authors hypothesized that a more chronic exposure may be required to compromise the functional integrity of the epithelium and increase leakiness. While the effects of chronic cigarette smoke exposures on TER have not been studied, damage to epithelial structure following chronic exposures was observed in rat and rabbit models (Duarte, Faria, Ceolin, Cestari, & Assis, 2006; Gaafar & Al-Mansour, 1981; Isik, Kalender, Yardimci, & Ergun, 2004). Vocal fold epithelium of rats exposed to 30 cigarettes per day for 25, 50, and 75 days demonstrated signs of hyperplasia (Duarte, et al, 2006).…”
Section: Vocal Fold Epithelial Barrier Injurymentioning
confidence: 99%
“…Authors hypothesized that a more chronic exposure may be required to compromise the functional integrity of the epithelium and increase leakiness. While the effects of chronic cigarette smoke exposures on TER have not been studied, damage to epithelial structure following chronic exposures was observed in rat and rabbit models (Duarte, Faria, Ceolin, Cestari, & Assis, 2006; Gaafar & Al-Mansour, 1981; Isik, Kalender, Yardimci, & Ergun, 2004). Vocal fold epithelium of rats exposed to 30 cigarettes per day for 25, 50, and 75 days demonstrated signs of hyperplasia (Duarte, et al, 2006).…”
Section: Vocal Fold Epithelial Barrier Injurymentioning
confidence: 99%
“…[10][11][12] Animal studies also revealed vocal fold changes, including hyperplasia, metaplasia, and keratinization, triggered by regular smoking. [13][14][15] The vocal fold is the most common site of laryngeal carcinoma, 16 and it is vulnerable to vapor produced by ENDS because the cord lies directly in the upper respiratory tract. We sought to evaluate the histopathologic effects of 4 weeks of exposure to vapor created by ENDS on the vocal fold mucosa of rats.…”
Section: Introductionmentioning
confidence: 99%
“…The causal relationship in which smoking has a direct effect on the change of the mucous membrane of the vocal cords has been verified by numerous animal experiments [29]. Rats exposed to second-hand smoking had significantly higher proportions of moderate and focal inflammation of the larynx than a control group [30].…”
Section: Discussionmentioning
confidence: 99%